Plant Protection Products to Control Alternaria Brown Spot Caused by Alternaria alternata in Citrus: A Systematic Review - Alfonso Garmendia; María Ferriol; Roberto Beltrán; Francisco García-Breijo; María Dolores Raigón; María Del Carmen Parra; Hugo Merle (Agronomy)
Alternaria Brown Spot (ABS) is one of the most critical diseases affecting susceptible mandarins worldwide, being a limiting factor in their cultivation. Although there are numerous reports on effective plant protection products against the disease, field control is failing. In the literature, some of the results are contradictory, depending on the study and experimental scale. Therefore, this paper aimed to analyze the empirical evidence to answer the following questions: (i) What plant protection products have been used to control ABS? (ii) What are the methodologies used to test the substances? (iii) Why is ABS field control failing? An extensive literature search was performed in five databases: WoS, Scopus, Google Scholar, PubMed, and SciELO. The search string used was “Alternaria alternata” AND “Citrus”. Records were classified into ten groups according to their main topic. Group 3 “microorganisms and natural substances” and group 4 “fungicides” were full-text reviewed for data extraction (98 reports). Details of the microorganisms, natural substances, and fungicides used against A. alternata, as well as summaries of the methodologies, are provided. During this research, we highlighted significant aspects that may be hindering the control of Alternaria alternata in citrus: long periods of fruit sensitivity, abundance and floatability of inoculum, rapid infections, the appearance of resistance to fungicides, moderate effectiveness inhibiting the germination of conidia, uncertainty about the times of application, and persistence of the products.